The computer graphics manual - Salomon, David , 1938- (Texts in computer science, 2011)
This book presents a broad overview of computer graphics (CG), its history, and the hardware tools it employs. Covering a substantial number of concepts and algorithms, the text describes the techniques, approaches, and algorithms at the core of this field